2011
DOI: 10.1021/nn202728f
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Photoconduction Sensitivity and Bandwidth for Lithographically Patterned Nanocrystalline Cadmium Selenide Nanowires

Abstract: Nanocrystalline cadmium selenide (nc-CdSe) nanowires were prepared using the lithographically patterned nanowire electrodeposition method. Arrays of 350 linear nc-CdSe nanowires with lateral dimensions of 60 nm (h) × 200 nm (w) were patterned at 5 μm pitch on glass. nc-CdSe nanowires electrodeposited from aqueous solutions at 25 °C had a mean grain diameter, d(ave), of 5 nm. A combination of three methods was used to increase d(ave) to 10, 20, and 100 nm: (1) The deposition bath was heated to 75 °C, (2) nanowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
86
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 67 publications
8
86
0
Order By: Relevance
“…For the most of the samples, the value of a is relatively close to 1, suggesting their near‐linear photocurrent–intensity dependence. According to previous study, the power‐law relationship between photocurrent and incident power density is related to the existence of surface carrier traps, and low concentration of surface traps will lead to near‐linear photocurrent–intensity dependence . Moreover, the I–t curves of the fabricated devices under illumination of 350 nm UV light at 0 V bias are shown in Figure d, from which the highest photocurrent of ≈2.5 pA and the highest on/off ratio of ≈320 are observed in 1% Sn 4+ ‐CuI/ZnO sample under 350 nm UV light switching, outperforming ZnO metal‐semiconductor‐metal (MSM) photodetector and CuI/ZnO sample (with on/off ratio of ≈12), thanks to their greatly decreased dark current and built‐in electric field.…”
Section: Resultsmentioning
confidence: 64%
“…For the most of the samples, the value of a is relatively close to 1, suggesting their near‐linear photocurrent–intensity dependence. According to previous study, the power‐law relationship between photocurrent and incident power density is related to the existence of surface carrier traps, and low concentration of surface traps will lead to near‐linear photocurrent–intensity dependence . Moreover, the I–t curves of the fabricated devices under illumination of 350 nm UV light at 0 V bias are shown in Figure d, from which the highest photocurrent of ≈2.5 pA and the highest on/off ratio of ≈320 are observed in 1% Sn 4+ ‐CuI/ZnO sample under 350 nm UV light switching, outperforming ZnO metal‐semiconductor‐metal (MSM) photodetector and CuI/ZnO sample (with on/off ratio of ≈12), thanks to their greatly decreased dark current and built‐in electric field.…”
Section: Resultsmentioning
confidence: 64%
“…2 while obeying the power law dependence I $ P a , where a is 0.64, 0.55, and 0.52 for the biases of 2 V, 3 V, and 4 V, respectively. It is concluded that this decrease of a was due to the effect of defects on carrier transportation, 14 namely that higher bias caused more defects to become involved in carrier transportation. Further discussion on the contribution of surface defects is given below.…”
mentioning
confidence: 99%
“…On one hand, the crack-free 2D ZnO IO nanofilms fabricated with the addition of CA have better connectivity and larger coverage on the substrate, thus causing stronger UV absorption than the broken one fabricated without CA. On the other hand, photocurrent may also increase with the grain size [29]. Since the nanofilms fabricated with the CA/ZA ratios of 0.2:1 and 1:1 have similar coverage and UV absorption, the increase in photocurrent probably comes from their rougher bottom with larger grain size.…”
Section: Photo-detecting Properties Of 2d Zno Io Film Devicesmentioning
confidence: 99%